An improved diffuse interface method for three‐dimensional multiphase flows with complex interface deformation. (3rd February 2020) - Zhang, Tongwei; Wu, Jie; Lin, Xingjian
Summary: An improved diffuse interface (DI) method is proposed for accurately capturing complex interface deformation in simulations of three‐dimensional (3D) multiphase flows. In original DI methods, the unphysical phenomenon of interface thickening or blurring can affect the accuracy of numerical simulations, especially for flows with large density ratio and high Reynolds number. To remove this drawback, in this article, an interface‐compression term is introduced into the Cahn‐Hilliard equation to suppress the interface dispersion. The additional term only takes effect in the interface region and works normal to the interface. The difference of the current method from the previous work is that the compression rate can be adjusted synchronously according to the magnitude of local vorticity, which is strongly correlated to the interface dispersion and changes with the computational time and interface position. Numerical validations of the proposed method are implemented by simulating problems of Laplace law, Rayleigh‐Taylor instability, bubble rising in a channel, and binary droplet collision. The obtained results agree well with the analytical solutions and published data. The numerical results show that the phenomenon of interface dispersion is suppressed effectively and the tiny interfacial structures in flow field can be captured accurately. Abstract : 1. An improved DI method with interface compression is proposed and validated. 2. Interface dispersion is suppressed effectively and properly by using the magnitude of local vorticity as the interface compression factor. 3. Tiny interfacial structure can be captured accurately in flow field.